Microstructural characterization of composite electrode materials in solid oxide fuel cells via image processing analysis - Bae, S.-M.; Jung, H.-Y.; Lee, J.-H.; Hwang, J.-H. (2010)
Among various fuel cells, solid oxide fuel cells (SOFCs) offer the highest energy efficiency, when taking into account the thermal recycling of waste heat at high temperature. However, the highest efficiency and lowest pollution for a SOFC can be achieved through the sophisticated control of its constituent components such as electrodes, electrolytes, interconnects and sealing materials. The electrochemical conversion efficiency of a SOFC is particularly dependent upon the performance of its electrode materials. The electrode materials should meet highly stringent requirements to optimize cell performance. In particular, both mass and charge transport should easily occur simultaneously through the electrode structure. Matter transport or charge transport is critically related to the configuration and spatial disposition of the three constituent phases of a composite electrode, which are the ionic conducting phase, electronic conducting phase, and the pores. The current work places special emphasis on the quantification of this complex microstructure of composite electrodes. Digitized images are exploited in order to obtain the quantitative microstructural information, i.e., the size distributions and interconnectivities of each constituent component. This work reports regarding zirconia-based composite electrodes.
Keywords: Cell performance; Charge transport; Complex microstructures; Composite electrode; Conducting phase; Constituent phasis; Digitized images; Electrochemical conversion; Electrode material; Electrode structure; High temperature; Micro-structural characterization; Microstructural information; Sealing material; Solid oxide; Stringent requirement; Thermal recycling; Work place; Conversion efficiency; Energy conversion; Energy efficiency; Gas fuel purification; Image analysis; Microstructure; Pollution control; Solid oxide fuel cells (SOFC); Waste heat; Zirconia; Electrochemical electrodes